2022
DOI: 10.1007/s10640-021-00640-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Strategies to Improve Municipal Solid Waste Management in Developing Countries: Experimental Evidence from Nepal

Abstract: Many cities in developing countries lack adequate drainage and waste management infrastructure. Consequently, city residents face economic and health impacts from flooding and waterlogging, which are aggravated by solid waste infiltrating and blocking drains. City governments have recourse to two strategies to address these problems: a) ‘hard’ infrastructure-related interventions through investment in the expansion of drainage and waste transportation networks; and/or, b) ‘soft’, low-cost behavioural intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, the limited allocation of budgets and resources for waste management prevents the implementation of comprehensive solutions (Carmen-Niño et al, 2023;Olukanni & Oresanya, 2018). Addressing this issue requires a multifaceted approach, including educational campaigns to raise awareness (Puertas et al, 2022), improving waste separation infrastructure (Nepal et al, 2023), collaboration with local authorities or organizations for efficient waste disposal (Budihardjo et al, 2023), and potentially integrating food waste reduction into the curriculum. Food waste can be interpreted as the loss of edible food at different stages of the food chain, including harvesting, production, processing, distribution and consumption (Zborowski & Mikulec, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the limited allocation of budgets and resources for waste management prevents the implementation of comprehensive solutions (Carmen-Niño et al, 2023;Olukanni & Oresanya, 2018). Addressing this issue requires a multifaceted approach, including educational campaigns to raise awareness (Puertas et al, 2022), improving waste separation infrastructure (Nepal et al, 2023), collaboration with local authorities or organizations for efficient waste disposal (Budihardjo et al, 2023), and potentially integrating food waste reduction into the curriculum. Food waste can be interpreted as the loss of edible food at different stages of the food chain, including harvesting, production, processing, distribution and consumption (Zborowski & Mikulec, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that waste segregation interventions at the source are effective [10,17,25,[57][58][59][60]. Some studies had a multi-group intervention group, with different strategies for each group to improve waste separation behavior [30,32,35,37,40,41].…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
“…Many cities in developing countries lack adequate drainage and waste disposal infrastructure. As a result, urban dwellers face the economic and health impacts of flooding and inundation, which are exacerbated by the infiltration of solid waste and the blockage of drains [10]. In the European Union (EU), 3.3% of respondents stated that they do not sort waste at all [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the government should strengthen public-private cooperation, attract multiple investments, and reduce the cost of government management of solid waste during the entire process. Moreover, the construction of ZW cities should also simultaneously receive more investment [17].…”
Section: Research On the Construction Strategy Of Zw Citiesmentioning
confidence: 99%